A synthesis of animal-mediated seed dispersal of palms reveals distinct biogeographical differences in species interactions - Muñoz, Gabriel; Trøjelsgaard, Kristian; Kissling, W. Daniel (Journal of biogeography, 2019)
Aim To synthesize published knowledge on palm–frugivore seed dispersal observations and to test whether broad‐scale differences in geographic coverage, diversity, composition and functional structure of plant–animal interactions emerge between biogeographical regions. Location Neotropics and Afrotropics. Methods We constructed a meta‐network for both regions by aggregating observations of pairwise palm–frugivore interactions from the primary literature. We assessed sampling completeness with accumulation curves and estimated knowledge gaps for individual palm species and geographic units within biogeographical regions. We compared the taxonomic composition as well as structural indices of regional interaction networks and tested whether functional trait matching (i.e., the relationship between palm fruit size and frugivore body size) differs between regions. Results A total of 750 unique pairwise interaction records were retrieved from the primary literature covering 340 frugivores and 126 palms. Sampling completeness of frugivore interactions within biogeographical regions and for individual palm species was low (often <50%), geographic coverage limited, and relative knowledge gaps were largest in areas with high palm species richness. Interaction diversity and network modularity was larger in the Neotropics than the Afrotropics. A positive fruit size–body mass relationship (i.e., functional trait matching) was statistically significant in the Afrotropics, but not in the Neotropics. Main conclusions Available data on palm–frugivore interactions suggest major biogeographical differences in ecological networks among regions, even when taking differences in palm species richness into account. The Neotropics showed a larger interaction diversity and more modular network structure than the Afrotropics. Broad‐scale morphological trait matching among plants and frugivores was only observed in the Afrotropics. The lack of a Neotropical trait matching relationship might be driven by the late Quaternary extinctions of mammalian megafauna in this region. Although our work has increased the digital availability of palm–frugivore interaction observations, massive knowledge gaps of interaction diversity remain in the tropics.